Application of Citric Acid and Packaging Type Selection in Preserving Stability of Homemade Tomato Sauce: Application of Citric Acid and Packaging Type Selection in Preserving Stability of Homemade Tomato Sauce - Jimmy Jimmy; Yuyun Yuniati (Food Science and Technology Journal (Foodscitech), 2023)
Tomatoes are horticultural product widely grown in Indonesia and consumed by societies. They contain minerals, vitamins, and bioactive compounds beneficial for health. Unfortunately, tomatoes quickly decline in quality, causing their post-harvest shelf life to be short. One attempt to prevent the wastage of tomatoes is to process them into sauce products. To extend the stability of tomato sauce, food-grade preservatives such as citric acid need to be added. Furthermore, different packaging also affects the stability of tomato sauce. This study used citric acid with varying concentrations of 0.05%, 0.10% and 0.15%. The packaging used included Clear Glass Bottles, Dark Glass Bottles, Clear Plastic Bottles, and Dark Plastic Bottles. The tomato sauce was evaluated by room storage for 30 days to investigate the stability of water content, acidity level, and total microbes. Adding 0.15% citric acid may be considered in preserving tomato sauce with a difference in increasing water content of 1.7%, a difference in decreasing pH of 0.1, and a difference in increasing total microbes of 1.4 cfu/g. Using a dark glass bottle may better protect tomato sauce from quality degradation.